DEVELOPMENT OF ANDROID STUDIO-BASED LEARNING MULTIMEDIA AS A SOURCE OF SELF-STUDY ON THE TOPIC OF THE DIGESTIVE SYSTEM - Hudson Sidabutar; Alloy Tifany Singarimbun (Universitas Negeri Medan, 2022)
This study aimed to determine the feasibility level of digestive system learning multimedia developed using Android Studio as a source of student self-study based on the responses of material experts, media experts, biology teacher, and students. The research used a 4-D model of instructional development design, including the define, design, develop, and disseminate stages, limited to the limited deployment stage to see students' classical learning completeness. Research preparation began in September – January 2022. Product trials are carried out at SMA Negeri 1 Kutabuluh. The results showed that the Learning Multimedia that had been developed was feasible to be used as a source of student self-study because it met the eligibility criteria with an average score of 4.3 from material experts who were included in the very good criteria, an average score of 4.4 from media experts who included in the very good criteria, the average score of 4.9 from the subject teachers included in the very good criteria, and the average score of 4.82 from the large group trial students who were included in the very good criteria. Classical learning completeness of students in a limited distribution got a percentage of 94%.